Gambaran Peresepan Obat Pada Pasien Penderita Infeksi Saluran Pernapasan Akut Di Puskesmas Tarogong Kabupaten Garut - Setiani, Andra Arista; Permana, Gin Gin Sugih; Suwinda, Dina Nirwana (LP4M STIKes Karsa Husada Garut, 2024)
Infeksi Saluran Pernafasan Akut (ISPA) is a major cause of infectious disease morbidity and mortality in the world. ARI is an acute inflammation of the upper and lower respiratory tract caused by microbial, bacterial or viral infection without or with lung parenchyma. ARI has a disease group with the highest absenteeism rate compared to other disease groups and is also suffered by many people. The purpose of this study was to determine the description of drug prescribing in patients with acute respiratory infections at the Tarogong Health Center, Garut Regency. This research method is descriptive with retrospective data collection, data collection is done by simple random sampling technique. The results of this study were patients with ISPA, which were mostly female patients with a percentage of 52.98% as many as 142 people and men with a percentage of 47.01% as many as 126 people. The data sample regarding the age of late adolescence 17-25 years is the most cases with a percentage of 22.38% as many as 60 people. Based on the classification of ARI drugs that are more widely used are antibiotics with a percentage of 29.77% as many as 268 people, analgesics - antipyretics with a percentage of 27.44% as many as 247 people, expectorants with a percentage of 20.33% as many as 183 people, antihistamines with a percentage of 13, 22% as many as 119 people, corticosteroids with a percentage of 8.22% as many as 74 people, bronchodilators with a percentage of 1% as many as 9 people. Based on the type of ISPA the most widely used drugs were amoxicillin with a percentage of 71.26% as many as 191 people, paracetamol with a percentage of 70.89% as many as 190 people, chlorpheniramine maleate with a percentage of 36.94% as many as 99 people. From these data, it can be concluded that female late adulthood suffers from ISPA, the most widely used drugs are amoxicillin, paracetamol, chlorpheniramine maleate, glyceryl guaiacolate, salbutamol and dexamethasone.